Psychiatrists and the Transformation of Juvenile Justice in Philadelphia, 1965–1972. (8th June 2018) - Raz, Mical
Abstract: In the late 1960s, Philadelphia psychiatrists evaluated every child who interacted with the city's juvenile courts. These evaluations had an important role in determining the placement and treatment of these children, and emphasized the therapeutic nature of the juvenile courts at the time. Relying on extensive case studies compiled by the Philadelphia Department of Public Welfare, this study reconstructs the roles of psychiatrists in the experiences of children interacting with the juvenile justice system, to shed light on a hitherto unknown aspect of these children's care. Gradually, the emphasis in juvenile justice shifted from a therapeutic approach to a more punitive one, from the mid 1970s and onwards. Yet the same structures of juvenile justice which allowed for individual discretion and "tailoring" of interventions to suit the child's perceived needs, rather than to fit the severity of his or her infraction, lost much of their therapeutic rationale. Still, many of these characteristics of the juvenile justice system, and in particular the practice of indeterminate sentencing, remain in place today. Questioning the role of mental health professionals in the creation and perpetuation of this flawed and often unfair infrastructure is an important first step in contemplating reforms.